2022
DOI: 10.1590/0102-311x00124921
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and 5-year all-cause mortality in older Chilean people

Abstract: We aimed to examine the degree to which social participation is associated with mortality risk in older adults in Chile. We used the Chilean National Survey on Elderly Dependency, which is linked to vital statistics, in order to obtain death records. Four proportional risk regression models were estimated. Even with controlled sociodemographic, economic, family, and health variables, older adults who participate in social activities had a 22% lower risk of death than those who do not participate. We concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…These findings partly support the stereotype embodiment theory, which hypothesizes that SPA utilizes multiple pathways to influence health and longevity [ 14 ]. Our findings also support social participation as a protective factor for mortality [ 44 46 ] and suggest that individual motivations may be significant facilitators of social participation [ 47 ]. Despite the importance of healthy lifestyle [ 36 , 48 ] and social participation [ 49 ] in pursuing healthy aging, only a small proportion of older adults practice them [ 48 , 50 ].…”
Section: Discussionsupporting
confidence: 74%
“…These findings partly support the stereotype embodiment theory, which hypothesizes that SPA utilizes multiple pathways to influence health and longevity [ 14 ]. Our findings also support social participation as a protective factor for mortality [ 44 46 ] and suggest that individual motivations may be significant facilitators of social participation [ 47 ]. Despite the importance of healthy lifestyle [ 36 , 48 ] and social participation [ 49 ] in pursuing healthy aging, only a small proportion of older adults practice them [ 48 , 50 ].…”
Section: Discussionsupporting
confidence: 74%
“…A population-based study in Chile, involving individuals aged >60 years, observed that subjects' participation in social activities had a 22% lower risk of death than those who did not participate during the 5-year study period. 16 The Nord-Trøndelag Health Study (HUNT), a longitudinal study with a mean follow-up of 8.15 years in Norway, demonstrated that the frequency of social participation of 0.5 to less than 1, 1 to less than 2, and 2 or more times per week significantly reduced the mortality risk by 18%, 31%, and 39%, respectively. 17 Shimatani et al also explored the association between the change of the frequency in social participation and all-cause mortality for individuals aged ≥60 years in Japan; they found that continued or decreased frequency of social participation was associated with a decreased risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the frequency of social participation in health maintenance. A population-based study in Chile, involving individuals aged >60 years, observed that subjects’ participation in social activities had a 22% lower risk of death than those who did not participate during the 5-year study period 16. The Nord-Trøndelag Health Study (HUNT), a longitudinal study with a mean follow-up of 8.15 years in Norway, demonstrated that the frequency of social participation of 0.5 to less than 1, 1 to less than 2, and 2 or more times per week significantly reduced the mortality risk by 18%, 31%, and 39%, respectively 17.…”
Section: Discussionmentioning
confidence: 99%